Creative writing teaching-learning practice in second language learning: a didactic study - Tracy BLOOR; Sara GREAVES (E-REA)
This contribution comprises a didactic analysis of a course in literary criticism and creative writing based on a programme of transcultural poetry and plurilingual creative writing activities loosely inspired by Oulipean writing constraints. First, the notions of jargon and thought style (Sensevy, Gruson, et Le Hénaff, 2019; Bloor, 2020; Bloor, 2022) serve to identify the epistemic potential of this course in relation to canonical cultural practices in the fields of literary criticism and creative writing.Second, a clinical (Foucault, 1963) approach serves to describe and explore empirical examples of class activity with two objectives: first, to identify the construction and appropriation of the knowledge at stake, second, to situate this knowledge in relation to canonical cultural practices. With the help of the notions of jargon and thought style, we will try to reveal how the students engage with practices that show an epistemic relation to canonical, knowledgeable practice. Our study also sheds light on the way in which the affect of the (M)other tongue might be harnessed to irrigate second language expression (Greaves & De Mattia-Viviès, 2022).